The summer of 1814 in Madrid and Pamplona - Ortuño Martínez, Manuel (Huarte de San Juan. Geografía e Historia, 2011)
When Fernando VII come back to Spain at 1814 it was established the most ferocious absolutism and began the repression to the followers of the 1812 Constitution. As a response to this royal action, increased the conspiracy centers, the political meetings and the subversion plans. The encounter in Madrid of the liberals constitutionalist commanders was in favour of a chaine of military “pronunciamientos” (insurrections) as that of the city of Pamplona, under de lidership of marechal Espoz and his nephew Xavier Mina, but it end as a final disaster. Here we present a long list of testimonies about this process so that Xavier Mina’s and other authors writings at the most immediate moment of the facts.